Animal Model for Determining the No-Effect Level of an Antimicrobial Drug on Drug Resistance in the Lactose-Fermenting Enteric Flora - Rollins, Larry D. (1975)
Mature beagles were fed a ground-meal diet containing 0, 2, or 10 μg of oxytetracycline per g for 44 days. The 10-μg/g diet resulted in a shift from a predominantly drug-susceptible population of enteric lactose-fermenting organisms to a multiply antibiotic-resistant population which peaked at 78% resistant organisms. Since a shift to drug-resistant organisms did not occur in the group fed 2 μg/g, the level of oxytetracycline that results in increased incidence of antibiotic resistance lies between 2 and 10 μg/g in this dog model. Rats and hamsters fed diets containing oxytetracycline (10 μg/g or greater) or dihydrostreptomycin (10 μg/g), and provided suspensions of drug-susceptible Escherichia coli, did not develop a population of antibiotic-resistant organisms.